Continuous positive airway pressure treatment from the prehospital field in a Japanese regional Doctor Car system - Ichiro Takeuchi; Shohei Imaki; Ryosuke Furuya; Masayuki Iwashita; Kohei Takahashi; Akihiro Furuya; Atsushi Yoshida; Takeru Abe (Acute Medicine & Surgery, 2023)
Abstract Background Continuous positive airway pressure (CPAP) therapy is an effective treatment for patients with severe heart failure, and certain guidelines recommend its early initiation. However, the current Japanese law strictly prohibits paramedics from administering this treatment. To demonstrate the efficacy and safety of prehospital administration of CPAP therapy, this study was conducted by the Yokohama Medical Control Council (Yokohama MC). Methods The Yokohama MC established a protocol for CPAP treatment and dispatched Doctor Cars to attend to patients with severe respiratory failure. The Boussignac CPAP system was installed in all Yokohama Doctor Cars, including Workstation‐type Doctor Cars and Hospital‐type Doctor Cars. Data from this study were collected and recorded in the Yokohama City Doctor Car Registry system from October 2020 to January 2022. Results The Doctor Car was dispatched 661 times, and CPAP therapy was administered to 13 patients in the prehospital field. It is important to note that the number of CPAP cases was lower than anticipated due to the coronavirus disease 2019 (COVID‐19) pandemic, given concerns about aerosol production. When assessing changes over time in oxygen saturation (SpO2), the median (interquartile range), excluding missing values, was 89% (83%–93%) without oxygen, 95% (94%–99.3%) with oxygen, and 100% (97%–100%) with CPAP. The differences between these groups were statistically significant with a p‐value of <0.0001. Respiratory distress was primarily attributed to heart failure in 10 patients (91%) and pneumothorax in 1 patient (9%). Notably, none of the patients’ conditions worsened after the use of CPAP. Conclusion We have detailed the administration of CPAP therapy in the prehospital field within a local city in Japan. To the best of our knowledge, this represents the inaugural report of a prospective observational study on the prehospital administration of CPAP therapy originating from Japan.